Bamboo cultivation: Opportunities and value addition for sustainable livelihoods - Raut, Prashant D.; Deshmukh, Aarti P.; Ilorkar, Vijay M. (Indian Farming, 2026)
Since 2017, the deregulation of bamboo harvesting and transport in India has promoted largescale bamboo cultivation on private farmlands. Bamboo is a highly versatile agroforestry species widely used in agriculture, horticulture, dryland farming, and rural households, generating significant rural employment. National demand for bamboo is rising, with added importance in biofuel production and as an eco-friendly alternative to plastics. It grows well in light soils, reduces soil erosion, and supports soil and water conservation, making it vital for climate resilience and sustainable land management.